RANCANG BANGUN KUNCI OTOMATIS MENGGUNAKAN POLA KETUKAN BERBASIS KETUKAN BERBASIS ARDUINO - Andri Budi Laksono; Diyah Ruswanti; Dwi Retnoningsih (JIMSTEK: Jurnal Ilmiah Sains dan Teknologi, 2021)
The development of technology and completeness of electronic equipment do not cause changes in society. It is indicated by the fact that the community still uses a simple key sistem. In opening and closing the door, they still use conventional keys such as child locks and sliding locks. This type of locking has been applied as a general locking method. However , the obstacles that occur in manual locking are the difficulty in opening the lock, for example, a jammed lock that requires extra effort to open. The use of manual locks is easy to duplicate, is prone to lose if taken away, and can allow other people to enter private homes or rooms. Therefore we need a door locking system that can provide ease of use from conventional locking, namely using automatic locking with a knock pattern. This research aims to design an automatic lock using an Arduino – based knock pattern, which provides another alternative in locking the door. This study uses a trial and error method, where the tool will continue to be tested until it is successfully implemented. This study uses a piezoelectric as a reader of vibrations resulting from a given beat. Furthermore, the given vibration will be stored by the system as a password to unlock the door. Relays are used to cut or supply voltage to the solenoid. Red led and green led is used as user indicators. Push – button is used to rest when entering a new password on the system. The result of this research is that the automatic unlocking system can identify the number of beats. If the number of beats detected is less than or equal to 20 (twenty), then the beats are correct, and the beats are wrong if the number of beats is more that 20 (twenty). The automatic unlocking system can also identift the slow and loud knocks when you want to unlock the door. The sound produced from a knock recorded using a smartphone device cannot be used as a door opener or cannot be used as an access control method. It is since the recorded knock sound does not provide sufficient vibration to be identified as a beat by the system.